2015
DOI: 10.4103/0366-6999.168063
|View full text |Cite
|
Sign up to set email alerts
|

Oenanthe Javanica Extract Protects Against Experimentally Induced Ischemic Neuronal Damage via its Antioxidant Effects

Abstract: Background:Water dropwort (Oenanthe javanica) as a popular traditional medicine in Asia shows various biological properties including antioxidant activity. In this study, we firstly examined the neuroprotective effect of Oenanthe javanica extract (OJE) in the hippocampal cornus ammonis 1 region (CA1 region) of the gerbil subjected to transient cerebral ischemia.Methods:Gerbils were established by the occlusion of common carotid arteries for 5 min. The neuroprotective effect of OJE was estimated by cresyl viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…It also restored the reduced activities of glutathione reductase and glutathione peroxidase, and the content of glutathione. In another related study, the neuroprotective effect of O. javanica extract in the hippocampal region of gerbils subjected to transient cerebral ischemia was investigated 32 . Results showed that the extract can protect neurons from transient ischemic damage and that the neuroprotective effect may be attributed to increased or maintained intracellular antioxidant enzymes.…”
Section: Neuroprotectivementioning
confidence: 99%
“…It also restored the reduced activities of glutathione reductase and glutathione peroxidase, and the content of glutathione. In another related study, the neuroprotective effect of O. javanica extract in the hippocampal region of gerbils subjected to transient cerebral ischemia was investigated 32 . Results showed that the extract can protect neurons from transient ischemic damage and that the neuroprotective effect may be attributed to increased or maintained intracellular antioxidant enzymes.…”
Section: Neuroprotectivementioning
confidence: 99%
“…A number of previous studies on neuroprotective effects by crude extracts derived from plants against cerebral ischemic injuries have used 200 mg/kg of dose. For example, for Chrysanthemum indicum Linné extract [8,11], Populus tomentiglandulosa extract [5,22], Oenanthe Javanica extract [1,23] and Glehnia littoralis extract [24] 200 mg/kg were used. In addition, these studies showed that treatment with dose of 100 mg/kg failed to protect neurons but administration of 200 mg/kg exhibited neuroprotective effects against cerebral ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…A temporary stop of blood supply to the whole brain causes ischemia/reperfusion injury and induces selective neuronal death in specifically vulnerable regions of the brain, such as the hippocampus [1,2]. In the hippocampus, the cornu ammonis 1 (CA1) field is a field vulnerable to ischemia/reperfusion injury [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…has been cultivated in the tropical and temperate regions of Asia for thousands of years and has long been widely used as a folk remedy for alleviating a wide spectrum of diseases. 16 For example, this plant is commonly used in Asia for the treatment of various types of diseases 17 including chronic and acute hepatitis, 18,19 jaundice, 20,21 fever, 22,23 hypertension, 21,24 abdominal pain, and urinary difficulties. 25,26 Several studies reported that dropwort has various functional activities in the liver against lipid peroxidation by bromobenzene 27 and hepatitis B virus activity.…”
Section: Introductionmentioning
confidence: 99%